Spatial Analysis Of Land Cover Change In Wae Batu Gajah Watershed, Ambon City In 2013, 2018 And 2023 Using Geographic Information System - Glendy Somae (Journal of Multidisciplinary Science, 2024)
This research presents a spatial analysis of land cover change in the Wae Batu Gajah Watershed, Ambon City, over three time periods, namely 2013, 2018, and 2023, using Geographic Information Systems (GIS). The data used for land cover change analysis are Landsat 7 satellite images for 2013 and satellite images for 2018 and 2023. Land cover is classified based on SNI 7465:2010 on Land Cover Classification which consists of built-up land, open land, non-agricultural land and water bodies. The analysis showed significant changes in land use patterns, including rapid urbanization, loss of natural habitats, and transformation of agricultural land. This information provides an important basis for sustainable regional planning and natural resource management. In addition, this study provides insights into the socioeconomic impacts of land cover change on local communities, and makes an important contribution to the understanding of environmental dynamics and better decision-making for the future of the Wae Batu Gajah watershed.